Exploring services science : 6th International Conference, IESS 2015, Porto, Portugal, February 4-6, 2015, Proceedings /: 6th International Conference, IESS 2015, Porto, Portugal, February 4-6, 2015, Proceedings. (2015) - Unknown
No abstract available